Kinetic Study of an Aerobic Digestion With Biomass Retention by Ultrafiltration Membranes - Khor, Ooi Hong (1997)

(untitled)
In this study, a 50 litre laboratory-scaled membrane anaerobic system (MAS ) combining ultrafiltration (UF) membrane with anaerobic reactor was used to treat palm oil mill effluent (POME) at ambient temperature. Six steady states were attained as part of a kinetic study. The results of steady state 4 (SS4) was adversely affected by a long shutdown due to pump leakage. The results of the five remaining steady states were successfully fitted, above 96%, by Monod, Contois, and Chen and Hashimoto models. Contois Model appeared to be the best at 99.7%. The microbial kinetic constants are Y=0.83gVS S/gCOD and b=0.15 day·I. Minimum solids retention time, ecmin obtained from the three simulation models range from 6-14.3days. Maximum total gas yield was measured at 0.621 litre/g COD at an organic loading rate (OLR) of 5.0 kgCOD/m3/d.%CH4 composition decreases from 75.7% at OLR of 1.8kgCOD/m3/d, to 62.3% at OLR of 6.0 kgCOD/m3/d. The percentages of COD removal were achieved between 99.0%-88.9% over a range of mixed liquor suspended solids of 10, 033-22, 175 mg/I. The final hydraulic and solids retention time, e and e have been reduced to 8.3_c days and 12.5 days, respectively during SS6. Under scanning electron microscope (SEM), the effective pores of the membrane was found to be pores larger than 0.1f-Lm. Layers of fibrous growth on the membrane surface increase separation efficiency. More efficient and frequent cleaning is required to inhibit membrane fouling and increase permeate flux. Overall, this study indicated that MAS is capable of treating higher OLR when Өc is maintained above 20 days.